2017
DOI: 10.15252/embr.201643146
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Atg8 recognition sites mediate Atg4 association with autophagosomal membranes and Atg8 deconjugation

Abstract: Deconjugation of the Atg8/LC3 protein family members from phosphatidylethanolamine (PE) by Atg4 proteases is essential for autophagy progression, but how this event is regulated remains to be understood. Here, we show that yeast Atg4 is recruited onto autophagosomal membranes by direct binding to Atg8 via two evolutionarily conserved Atg8 recognition sites, a classical LC3-interacting region (LIR) at the C-terminus of the protein and a novel motif at the N-terminus. Although both sites are important for Atg4-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 56 publications
3
72
0
Order By: Relevance
“…LIR2/APEAR in Figure 1), is essential for normal progression of autophagy. More precisely, the corresponding Atg4 mutant variant was not efficiently recruited to autophagosomal membranes and displayed a strong impairment in Atg8-PE deconjugation causing a decrease in autophagic flux and also a reduction in autophagosome size [2]. These data confirmed earlier findings showing that the autophagosome size is determined by the amount of available cytosolic Atg8,…”
Section: Franziska Kriegenburg and Fulvio Reggiorisupporting
confidence: 88%
See 3 more Smart Citations
“…LIR2/APEAR in Figure 1), is essential for normal progression of autophagy. More precisely, the corresponding Atg4 mutant variant was not efficiently recruited to autophagosomal membranes and displayed a strong impairment in Atg8-PE deconjugation causing a decrease in autophagic flux and also a reduction in autophagosome size [2]. These data confirmed earlier findings showing that the autophagosome size is determined by the amount of available cytosolic Atg8,…”
Section: Franziska Kriegenburg and Fulvio Reggiorisupporting
confidence: 88%
“…We confirmed these data in vitro, where this mutant Atg4 variant bound to recombinant (non-lipidated) Atg8 as wild type Atg4. We thus identified a distinct region in yeast Atg4, which does not act like a classical LIR motif but rather is particularly important for the association of Atg4 with lipidated Atg8 (Atg8-PE) and hence named it APEAR (Atg8-PE association region) [2]. In our study, we also confirmed that a putative LIR sequence at the C-terminus of Atg4 (i.e.…”
Section: Editorialsupporting
confidence: 79%
See 2 more Smart Citations
“…LC3s and GABARAPs play critical roles in facilitating the recruitment of cargo receptors and other autophagy proteins to autophagosomes by directly interacting with these proteins through conserved LC3‐interacting regions (LIRs) (Johansen & Lamark, ). After fusion with lysosomes, the fraction of LC3/GABARAP localized on the luminal side of autophagic vesicles is degraded in the lysosomes together with cargo receptors and substrates, while LC3/GABARAP present on the cytosolic face is released by Atg4 protease (Abreu et al, ).…”
Section: Introductionmentioning
confidence: 99%